Use of cosmetology and facial aesthetic medicine treatments by medical students (Journal of Face Aesthetics, 2021)
Introduction. There is an increase in the popularity of aesthetic treatment among increasingly younger groups of people, which also includes medical students. Their decisions are often dictated by their own acquired knowledge in this area of expertise.Aim. To estimate the number and determine the age threshold for the use of cosmetology and facial aesthetic medicine among Polish and English-speaking students.Material and Methods. The statistical analysis included 240 questionnaires (175 females and 65 males) addressed to Polish and English-speaking students in 3rd, 4th, and 5th year studies within the field of dentistry at the Medical University of Poznań in 2019 and 2020. The Pearson chi-squared test was performed to determine the significance of this test (p
Keywords: aesthetic medicine; facial aesthetics; cosmetology; survey research